2014
DOI: 10.1155/2014/638142
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Toxicological Assessment of Pharmaceutical Wastewater from the Lagos Megacity, Nigeria

Abstract: We conducted a microbiological and toxicological profiling of a pharmaceutical wastewater, one of the major wastes entering the Lagos lagoon. The morphological characterization of seven bacterial isolates from the wastewater indicated that 4 of them were gram positive bacilli while 3 were cocci of both gram reactions. The bacterial isolates exhibited varying degrees of enzyme activities but most were able to hydrolyze starch to yield amylase. Only 3 of the isolates showed prospects as antibacterial agents, giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…The physicochemical properties of the multivitamin production effluent showed that alkalinity (118 mg/L), total dissolved solids (313 mg/L) and dissolved oxygen (11.0 mg/L) were high. This is similar to the report of Obasi et al, (2014) and Agboola and Fawole (2014). The high alkalinity could cause fish death, damage to outer surfaces like gills, eyes, and skin and an inability to dispose metabolic wastes thereby, increasing ammonia which can Plate 3.…”
Section: Discussionsupporting
confidence: 93%
“…The physicochemical properties of the multivitamin production effluent showed that alkalinity (118 mg/L), total dissolved solids (313 mg/L) and dissolved oxygen (11.0 mg/L) were high. This is similar to the report of Obasi et al, (2014) and Agboola and Fawole (2014). The high alkalinity could cause fish death, damage to outer surfaces like gills, eyes, and skin and an inability to dispose metabolic wastes thereby, increasing ammonia which can Plate 3.…”
Section: Discussionsupporting
confidence: 93%
“…32 In addition, Obasi et al, similarly reported the presence of zinc and nickel in pharmaceutical waste water from Lagos Metropolitan Area. 33 These metals are known to be readily soluble in water, which makes them available for aquatic life to take up. These metals can also be taken up into the fat tissues of aquatic organisms and become magnified along the food chain, which may lead to detrimental health issues if the there is no proper check on industrial discharges.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the pollutants in questions range from pharmaceuticals, chemical compounds, metals, media remnants, antibiotics, disinfectants, radioactive isotopes, and stock cultures [9]. In some instances, some pharmaceuticals present in hospital wastewater have been implicated in causing the disruption of the endocrine system, impairment of the reproductive system and sex reversal in some aquatic species [10]. The discharge of this wastewater has led to the build-up of nutrients in the receiving aquatic ecosystem, leading to eutrophication [7].…”
Section: Wastewater From Healthcare Systems (Composition and Microbio...mentioning
confidence: 99%